Stress inducible proteomic changes in capsicum annuum leaves - Mahajan, Neha S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Plant Physiology and Biochemistry, 2014)
Herbivore attack induces defense responses in plants, activating several signaling cascades. As a result, molecules deterrent to the herbivores are produced and accumulated in plants. Expression of defense mechanism/traits requires reorganization of the plant metabolism, redirecting the resources otherwise meant for growth. In the present work, protein profile of Capsicum annuum leaves was examined after herbivore attack/induction. Majority of proteins identified as differentially accumulated, were having roles in redox metabolism and photosynthesis. For example, superoxide dismutase and NADP oxidoreductase were upregulated by 10- and 6-fold while carbonic anhydrase and fructose-1,6-bisphosphatase were downregulated by 9- and 4-fold, respectively. Also, superoxide dismutase, NADPH quinone oxidoreductase and NADP dependent isocitrate dehydrogenase transcripts showed a higher accumulation in induced leaf tissues at early time points. In general, proteins having role in defense and damage repair were upregulated while those involved in photosynthesis appeared downregulated. Thus metabolic reconfiguration to balance defense and tolerance was evident in the stress-induced leaves. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Capsicum annuum; Oxidative stress; Wounding